2002
DOI: 10.1161/01.cir.0000025610.14665.21
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of Sympathetic Neural Hyperactivity After Uncomplicated Acute Myocardial Infarction

Abstract: Background-Little information is available on sympathetic activity after acute myocardial infarction (AMI), despite the belief that sympathetic drive is important in relation to morbidity and mortality. Indirect indices such as plasma catecholamines are transiently elevated after uncomplicated AMI, whereas other prognostically important autonomic indices may be affected longer. We planned to quantify central sympathetic output to the periphery after uncomplicated AMI and to investigate its progress over time. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
0
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 45 publications
(40 reference statements)
3
75
0
5
Order By: Relevance
“…The same protocol was performed between the hours of 9:00 AM and 12:00 noon for all groups as previously reported. 4 Subjects were asked to have a light breakfast and to empty their bladder before commencing the study and were requested to avoid alcohol, nicotine, and caffeine products for 12 hours before investigation.…”
Section: General Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…The same protocol was performed between the hours of 9:00 AM and 12:00 noon for all groups as previously reported. 4 Subjects were asked to have a light breakfast and to empty their bladder before commencing the study and were requested to avoid alcohol, nicotine, and caffeine products for 12 hours before investigation.…”
Section: General Protocolmentioning
confidence: 99%
“…ympathetic hyperactivity has been shown to occur early after acute myocardial infarction (AMI), [1][2][3][4] although very little is known about whether its magnitude differs between anterior wall (ant-AMI) and inferior wall (inf-AMI) infarction. This information is important because it may be relevant to the prognosis after AMI and to the mechanisms of associated sympathetic activation.…”
mentioning
confidence: 99%
“…2 This state of increased sympathetic tone seems to persist beyond the ischemic event. 1 To our knowledge, there are no studies that have shown that reversal of ischemia by PCI reduces central sympathetic tone. In our patient group, sympathetic nervous system activity was indeed clearly increased.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The most likely explanation is stimulation of sympathetic afferents in the myocardial wall due to ischemia-induced release of a number of afferentstimulating substances. 3,4 If the ischemic stimulus is strong enough, a reflex increase in central sympathetic output occurs, despite current pharmacological interventions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation